Prevalence and associated factors of post-stroke depression among patients on follow-up at medical referral clinics of Bahir Dar city public specialized hospitals - Ermiyas Yemane Debebe; Mulugeta Biyadgie; Hanamariam Abebe Chekol; Lakew Asmare; Zeamanuel Anteneh Yigzaw (BMC Neurology)
Abstract Background Post-stroke depression is among the most common neuropsychiatric complications in stroke survivors. Post-stroke depression is commonly under-recognized and under-treated. This study aimed to assess the prevalence and associated factors of post-stroke depression among patients on follow-up at medical referral clinics of Bahir Dar City public specialized hospitals. Method An institutional-based prospective cross-sectional study was conducted from September to December 2023 on 394 patients. Public Health Questionnaire-9 was used to diagnose depression. Data was checked for cleanness manually and then exported to SPSS version 25 software for analysis. A systematic randomized sampling method was used to identify study participants. Bivariate and multivariate logistic regression analysis was performed to identify independent predictors of post-stroke depression. A p-value less than 0.05 is considered as significant with a 95% confidence interval. Result The overall prevalence of post-stroke depression was found to be 42.9%. Employment status (AOR = 0.282, 95% CI: 0.112–0.709 C, P-value = 0.007), depression before stroke (AOR = 3.237, 95% CI: 1.098–9.544, P-value = 0.033), ischemic heart disease (AOR = 4.090, 95% CI: 1.745–9.583, P-value = 0.001) and physical disability (AOR = 4.051 95% CI: 2.239–7.332, P-value = 0.000) were found to be statistically significant independent predictors of post-stroke depression (PSD). Conclusion The prevalence of post-stroke depression was found to be high relative to other similar studies. Patients with known depression before stroke, ischemic heart disease, and significant physical disability were at a higher risk of developing PSD. Employed patients had less risk of developing PSD. Sufficient and comprehensive evaluation of stroke patients for depression is recommended.